MENGENAL WISATA KESEHATAN PELAYANAN MEDIS DI DAERAH ISTIMEWA YOGYAKARTA - Arisanti, Yuli (Kepariwisataan: Jurnal Ilmiah, 2019)
Health tourism particularly medical tourism has been an attention by Indonesian government. Many Indonesian citizens travel overseas to get medical treatment and it has made millions dollars of money went out of country. Indonesia works to mitigate the loose of money because of the citizens seeking medical treatment overseas. Consumer motivations in health tourism is various such as to get a better health facilities at better price. This research sets out to find out hospitals in Yogyakarta that provides health tourism service, and also the potential medical treatment in Yogyakarta. Literature studies, observation and interview are conducted to collect data and information. This research finds there are two hospitals in Yogyakarta have been focusing and experiencing in health tourism. The potential medical treatments are infertility, skin and beauty care, urology and all the medical services provided by these two hospitals. Elaboration and cooperation among stakeholders in health tourism need to be continuously improved to prepare Yogyakarta as health tourism destination. The quality of human resources should also be improved. Keywords: health tourism, medical tourism, Yogyakarta, consumer motivation